Combined use of VA-ECMO and IMPELLA (ECPELLA) as a possible strategy to improve outcomes in patients who underwent E-CPR. (25th November 2020) - Unoki, T; Tamura, Y; Nakayama, T; Kametani, M; Minami, Y; Konami, Y; Suzuyama, H; Inoue, M; Yuhu, T; Kodama, K; Yamamuro, M; Taguchi, E; et al.
Abstract: Background: Extracorporeal Cardio-Pulmonary Resuscitation (E-CPR) is an effective tool for patients with refractory cardiac arrest (CA). Since VA-ECMO provides strong afterload, IABP is often used to increase left ventricular load. Recently, in Japan, the effectiveness of VA-ECMO in combination with IMPELLA, a forward flow mechanical circulatory support device (ECPELLA) is gaining attention. Purpose: We investigated usefulness of ECPELLA in patients with refractory CA. Method: We reviewed 133 patients that had E-CPR from January 2012 through January 2020 mean age: 67±15 years, male 65%, Out of hospital Cardiac Arrest (OHCA) 35%, Acute coronary Syndrome (ACS) 54%. We divided these patients into ECMO with IMPELLA (ECPELLA group), ECMO with IABP (IABP group) and ECMO alone (ECMO alone group). The primary endpoint is 30-day survival and good neurological prognosis defined as CPC (cerebral performance categories) 1 or 2. Result: During the study period, of the 133 patients, there were 20 in the ECPELLA group, 78 in the IABP group, 35 in the ECMO alone group. There were no significant differences in age in all three groups. There were more males, shockable rhythm, OHCA and ACS in the ECPELLA and IABP groups compared to the ECMO alone group. But there was no significant difference between the ECPELLA and IABP groups. Compared with other groups, ECPELLA had the shortest time from cardiac arrest to ECMO placement. Regarding endpoints, the rate of 30-day survival and favorable neurological prognosis were higher in the ECPELLA group, followed by the IABP group and then the ECMO alone group. (ECPELLA: 55% vs. IABP: 23% vs. ECMO alone: 9%; P=0.0009, ECPELLA: 35% vs. IABP: 13% vs. ECMO alone: 9%; P=0.04) Next, Kaplan Meier analysis was performed to analyze 30-day all-cause mortality. The ECPELLA group had a significantly higher survival rate (P=0.01 by log-rank test). Multivariate cox proportional hazard analysis including the age, OHCA, shockable rhythm, ACS, Collapse-to-ECMO under 60 min revealed that the age (hazard ratio [HR], 1.28 (10 years increase), 95% confidence interval [CI], 1.08–1.53, P=0.004) and Collapse-to-ECMO under 60 min (HR, 0.37, 95% CI, 0.21–0.68, P=0.001) or ECPELLA (HR, 0.46, 95% CI, 0.20–0.694, P=0.03) were significantly associated with mortality. Conclusion: ECPELLA used with E-CPR is an effective tool to improve mortality and neurologic status. Funding Acknowledgement: Type of funding source: None